Financiamento do ensino superior no contexto da emenda constitucional nº 95/2016: o caso da UFES - Rosa, Náiade Nicoli (2021)
Introduction: Faced with the Brazilian economic scenario marked by a crisis that began in 2014 and extended strongly in the years 2015 and 2016, the country entered a recession and adopted new economic measures. In the midst of these measures, the New Tax Regime (NRF) was established, instituted by Constitutional Amendment 95 of December 15, 2016 (EC 95), also called the amendment of the expenditure ceiling. because it establishes limits for the expenses of the Federal Government bodies. In view of the enactment of such an amendment, the reflexes are beginning to be perceived mainly in the promotion of public policies. In the educational field, there is an effort to maintain the legal guarantees of Education funding, as well as an attempt to expand these resources. On the other hand, the government has been investing in the idea of untying financial resources for the maintenance and development of education, especially for this study, higher education. From this, the following question arises: what are the implications for the financing of higher education at the Federal University of Espírito Santo in view of the measures established by the Constitutional Amendment 95 of 2016? In this sense, this study had as main objective to ascertain the budgetary implications through the approval of EC 95 at the Federal University of Espírito Santo. The methodology used was the case study with a mixed approach, that is, quantitative and qualitative simultaneously, using descriptive statistics. As a result of this study, it was possible to observe that the UFES, as well as the MEC and the federal public higher education had budgetary losses with the advent of EC 95. The conclusion of this study was an analysis of the budgetary and financial impact of UFES in the period 210 to 2020 and the UFES Transparency Portal project, which aims to assess budgetary losses in the institution from EC 95, suggest a tool to provide the academic community and anyone interested in budget and financial information about UFES in simple language, formalizing the technical product.